ANALISIS BAURAN PEMASARAN UNTUK MENGETAHUI PENYEBAB TIDAK TERCAPAINYA TARGET PENJUALAN KARTU PERDANA IM3 PADA PT. INDOSAT Tbk. CABANG PEKANBARU - Nofrizal, Nofrizal (Jurnal Daya Saing, 2019)
In line with the rapid development of mobile phones, the competition among companies that offer cellphone cards is also called mobile operators. Currently there are 3 Global System for Mobile Communication (GSM) technology operators that have the largest market share, namely PT. Telkomsel, PT. Indosat and PT. Excelcomindo. The object of this research is PT. Indosat Pekanbaru branch. The purpose of this research is to find out the factors that have caused the achievement of IM3 starter card sales target at PT. Indosat Tbk Pekanbaru branch. Respondents from this study were students and the general public who used an IM3 starter pack for at least 3 consecutive months. The number of samples was 99 people with accidental sampling technique. The results of the study address the factors of the promotion of the IM3 prime card of PT. Indosat Tbk Pekanbaru Branch is the cause of the sales target not being achieved due to get the lowest value compared to other factors with a score of 3.64 Key Word: Product, Price, Promotion, place, Telecomunication